Improving high school students’ basic skills to analyze nutrition value labels of food products - Sulandjari, Siti; Indrawati, Veni; Sholihah, Lini; Pratama, Satwika Arya (IAIN Madura, 2023)
The nutrition label is important for commercial food products to be available in the market and is compulsory to be included in the package. This paper's objective is to present the training description and its effectiveness in improving students' knowledge regarding creating nutrition labels for food products based on BPOM regulation. An experimental with Community Based Research approach was used in this study. A total of 26 female students from Senior High School (SHS) 1 Karas were involved in a one-day training. Based on the observation, most students were fairly participated during the training (33.4%). There was a significant increase in the respondents' knowledge after vs. before the training (45.77 vs. 32.69, p-value<0.05). We found a trend that students who performed low participation tended to have a lower post-test score. The student's participation during the training seems to correlate positively with the post-test score. We confirmed this relationship with Spearman rho's test, in which the correlation was 0.85 (p-value<0.05), suggesting that the correlation was strong enough. Our study demonstrated that one training session had a significant impact on the first-grade SHS students' knowledge of analyzing the nutrition value label on the food product. Engaging students to participate in the class actively can enhance the student's understanding. More intensive training with innovative methods that facilitate shy students.